The Early English Novel: Tradition and Newspapers - Polić-Jurković, Vanja (Array, 2011)
The article explores some of the social and cultural contexts in which the early English novel emerged at the turn of the 18th century: firstly, the Quarrel of the Ancients and the Moderns that infused the English society of the time and the ways in which it was reflected in the emergence of the novel on the literary scene, its acceptance by the wide reading audience and its neglect by the learned circles. Secondly, the article discusses the influence of newspapers and periodicals on the development of the novel, not only intrinsically through style and discourse, but also extrinsically, by placing the novel into the 18th-century cultural consciousness. The beginnings of the novel are, thus, discussed with regard to the hieratic and demotic aspects of the early 18th-century culture as they appeared in the printed materials that surrounded them.